ANALYSIS OF THE MAGNETIC STORMS CATALOG FOR MONITORING RADIO SOURCE FLUXE DATA WITH THE URAN-4 RADIO TELESCOPE IN THE ODESA MAGNETIC ANOMALY ZONE - L. I. Sobitnyak; M. I. Ryabov; M. I. Orlyuk; A. L. Sukharev; A. O. Romenets; Yu. P. Sumaruk; A. A. Pilipenko (Radio Physics and Radio Astronomy, 2020)
Purpose: Compilation of a digital catalog of magnetic storms in the Odesa magnetic anomaly zone in order to find the reasons for possible changes in the radiation fluxes of cosmic radio sources, according to observations at the URAN-4 radio telescope.